Left Heart Decompression on Veno-Arterial Extracorporeal Membrane Oxygenation in Children With Dilated Cardiomyopathy and Myocarditis: An Extracorporeal Life Support Organization Registry Review. Issue 12 (December 2021) - Choudhury, Tarif A.; Ofori-Amanfo, George; Choi, Jaeun; Eisenberg, Ruth E.; Rycus, Peter; Medar, Shivanand S.; Aydin, Scott I.
Abstract : OBJECTIVES: To describe the association between left heart decompression on veno-arterial extracorporeal membrane oxygenation and survival in patients with myocarditis and dilated cardiomyopathy. The secondary outcome is to study association of left heart decompression with survival in children with myocarditis compared with those with dilated cardiomyopathy. DESIGN: Retrospective study of a multicenter registry database. SETTING: Data reported to Extracorporeal Life Support Organization from international extracorporeal membrane oxygenation centers. PATIENTS: Patients less than or equal to 18 years old with a diagnosis of myocarditis or dilated cardiomyopathy receiving extracorporeal membrane oxygenation. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: A total of 1, 438 pediatric extracorporeal membrane oxygenation runs were identified. Thirty-seven percent of the patients had myocarditis ( n = 532), whereas the rest had dilated cardiomyopathy. Survival to hospital discharge was 63%. Median extracorporeal membrane oxygenation duration was 148 hours with interquartile range (84–248 hr). Nineteen percent of patients ( n = 274) had left heart decompression. Multivariable analysis revealed using left heart decompression (adjusted odds ratio, 1.42; 95% CI, 1.06–1.89; p = 0.02), e-cardiopulmonary resuscitation (adjusted odds ratio, 0.63; 95% CI, 0.51–0.79; p < 0.001), higher pH (adjusted odds ratio, 3.69; 95% CI, 1.80–7.53; p < 0.001), and diagnosis of myocarditis (adjusted odds ratio, 1.69; 95% CI, 1.35–2.08; p < 0.001) were associated with greater odds of survival. In the multivariable analysis for patients with dilated cardiomyopathy, left heart decompression failed to reveal a significant association with survival (20% among survivors vs 17% among nonsurvivors, 95% CI, –2.2% to 8.0%). Meanwhile in patients with myocarditis, the multivariable analysis failed to exclude the possibility that left heart decompression was associated with up to a three-fold greater odds of survival (adjusted odds ratio, 1.77; 95% CI, 0.99–.15). CONCLUSIONS: Retrospective review of the Extracorporeal Life Support Organization registry revealed an association between left heart decompression and greater odds of survival in children with myocarditis and dilated cardiomyopathy on extracorporeal membrane oxygenation. When comparing patients with dilated cardiomyopathy against those with myocarditis, we could not exclude a three-fold greater odds of survival associated with the use of left heart decompression. This finding warrants further prospective evaluation.